Barriers in implementing research findings in cancer care: the Greek registered nurses perceptions - Patiraki, Elisabeth; Karlou, Chrysoula; Papadopoulou, Despina; Spyridou, Ageliki; Kouloukoura, Chrysoula; Bare, Elpida; Merkouris, Anastasios (My University, 2004)
This study explored Greek nurses’ perceptions of the barriers to research utilization faced in every day practice. The barriers between nurses working in cancer and general hospitals, as well as between those employed at central and provincial hospitals were compared. The study used a cross-sectional design and data were collected using the “Barriers Scale” (Funk et al., 1991a, Applied Nursing Research, 4, 39–45). A convenience sample of 301 nurses was randomly selected from 12 hospitals in Greece. The two key barriers identified were related to the ‘availability of research findings’. English language was perceived to range between moderate and major barrier for the vast majority of participants (n=231, 78%). Nurses surveyed indicated the presentation of research findings as the greatest barrier while the characteristics of nurses themselves were perceived as the least important one. No significant differences were found between types of hospitals (cancer/general) and geographical areas (central/provincial). Some differences, however, were observed in relation to specific items of the scale such as feeling isolated from ‘research-knowledgeable’ colleagues and having insufficient time to implement new ideas. The observations reported here appear to agree with the findings in mainstream literature. The results suggest that more emphasis should be given in research methodology, statistics and critical appraisal skills at all levels of nursing education, and that efforts should be made towards increasing research availability and creating supportive environments for implementation of research findings.
Keywords: Cancer--Nursing; Barriers to research implementation; Nursing